ANALISIS KINERJA KOPERASI DAN DAMPAKNYA TERHADAP KESEJAHTERAAN ANGGOTA (Studi Pada Koperasi Usaha Manunggal Desa Seresam Kecamatan Seberida Kabupaten Indragiri Hulu) - Aris Triyono; Suwaji Suwaji; Marwan Indra Saputra (JURNAL MANAJEMEN DAN BISNIS, 2019)
Cooperatives are not only expected to be able to produce residual business results in each period, investment activities carried out by cooperatives must be effective in producing positive added value, therefore cooperatives need to be managed as well as possible so that they can grow into a strong and independent organization, with the best performance and ability raise the welfare of its members. This research is in Kopsa. Manunggal Enterprises, Seresam Village, Seberida District, Indragiri Hulu Regency, Riau Province. The purpose of this research is to find out and analyze Cooperative Performance and Its Impact on Members' Welfare. This study used a quantitative descriptive approach, the data the authors use are primary and secondary data, primary data obtained through questionnaires distributed to research respondents to measure Cooperative Performance and Members' Welfare Levels, and secondary data obtained directly from Kopsa. Manunggal Enterprises in the form of financial statement documents. The analytical tool used to measure / assess financial performance with the viewpoint of Economic Value Added (EVA. Cooperative Performance is measured based on 6 (six) indicators of Cooperative Performance, namely: Business Entity Activities, Business Performance, Members' Cohesiveness and Participation, Orientation to Member Services, Services to the Community and contribution to Regional Development Welfare level is measured based on aspects of family income, expenditure on consumption, employment status, health conditions and the ability to access other basic needs.The results of descriptive analysis show Kopsa. Manunggal Enterprises including Cooperatives that are performing well, households Farmers who are members of Kopsa, Manunggal Enterprises are included in the welfare category and the regression analysis conducted shows that the regression coefficient is positive, meaning that there is a positive impact between Cooperative Performance and Welfare. The better the Cooperative Performance will have a positive impact on increasing yes the welfare of members, this can happen because of the monoculture community farming patterns where the main source of income of the village community, especially Kopsa members. Manunggal Business is a commodity of oil palm plantations managed by cooperatives, so the cooperative performance variable becomes very influential in influencing the ease of service, distribution of member income, access to credit and other ease of convenience.